Transcriptomic analysis reveals peripheral pathway in 3-phenoxybenzoic acid degradation by Aspergillus oryzae M-4. (1st January 2023) - Hu, Kaidi; Li, Jianlong; Zhao, Tianye; Zhou, Qiao; Li, Qin; Hu, Xinjie; Han, Guoquan; Li, Shuhong; Zou, Likou; Liu, Shuliang
Abstract: As a major intermediate metabolite of synthetic pyrethroids, the occurrence of 3-phenoxybenzoic acid hinders the decomposition of the parent pesticide and poses uncertain risks to environmental ecology and living organisms. Strain Aspergillus oryzae M-4 was previously reported to degrade 3-PBA and several substances were identified as downstream transformation products (TPs). But the mechanism underlying the cleavage of ether bond remains largely unclear. Here, we attempted to address such concern through identifying the peripheral TPs and analyzing transcriptomics, coupled with serial batch degradation experiments. Analysis results of chromatographic/mass spectrometry suggested that 3-PBA underwent twice hydroxylation, to yield mono- and dihydroxylated 3-PBA successively. In parallel, a mutual transformation between 3-PBA and 3-phenoxybenzyl alcohol (3-PBOH) also existed. The proposal of peripheral pathway represents an important advance towards fully understanding the whole 3-PBA metabolism in M-4. A specific altered metabolization was found for the first time, that is, resting cells of M-4 skipped the reduction step and initiate hydroxylation directly, by comparison with growing cells. Transcriptome analysis indicated that 3-PBA induced the up-regulation of genes related to energy investment, oxidative stress response, membrane transport and DNA repair. In-depth functional interpretation of differential expression genes suggested that the generation 3-PBOH and hydroxylated 3-PBA may be due to the participation of flavin-dependent monooxygenases (FMOs) and cytochrome P450 (CYP450), respectively. This study provides new insight to reveal the biodegradation mechanism of 3-PBA by A . oryzae M-4. Graphical abstract: Image 1 Highlights: Reduction and hydroxylation constitute the peripheral degradation pathway of 3-PBA. The growing cells of M-4 could reduce 3-PBA to 3-PBOH. Candidate genes involving in peripheral degradation of 3-PBA were proposed.